Suspiria. Mythical imaginaries of the terrible mother: The abject and corporeal in the horror films of Luca Gudagnino - Castelli Olvera, Azul Kikey (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
Objective: from interpretive hermeneutics, analyze the social imaginaries about the terrible mother, represented in the film Suspiria, by Luca Guadagnino. Methodology: an interpretive method is used where Morris’s sign proposal, Jung's archetypes, Durand's anthropological structures, Kristeva’s powers of horror, and the myth of Cortés’s castrating woman are taken up. Results: the mass media as cathartic cultural spaces, reiterate and reinterpret archetypes through the representation of myths, where sometimes the feminine is linked to power, the corporeal, the abject, and the social imaginary of the terrible mother.